Art is Books : Kunstenaarsboeken. - Aguiar, Fernando; André, Carl; Baroni, Vittore; Bentivoglio, Mirella; Bleus, Guy; Ciani, Piermario; Crozier, Robin; Deisler, Guillermo; Fontana, Giovanni; François, Charles; Fricker, H. R.; Germany, Albrecht D.; et al. (Hasselt : Provinciale Centrale Openbare Bibliotheek, 1991)
Oliveira, José ; Barrile, Paolo ; Aguiar, Fernando ; d., albrecht ; Banana, Anna ; Baroni, Vittore ; Benon, Jean-Pierre ; Bentivoglio, Mirella ; Blaine, Julien ; Bleus, Guy ; Bloch, Mark ; Bustamante, Maris ; Christo ; Cohen, Ryosuke ; Crozier, Robin ; Cuciniello, Natale ; Deisler, Guillermo ; de Jonge, Ko ; Denti, Giuseppe ; Eriksson, Leif ; Evans, John ; Fontana, Giovanni ; Formentini, Giacinto ; Frangione, Nicola ; Gerlovin, Rimma & Valery ; Groh, Klaus ; Held, John ; Hubaut, Joel ; Johnson, Ray ; Kocman, J.H. ; Lorenzi, Lydia ; Maciunas, George ; Maggi, Ruggero ; Ullrich, Richard Meade & Terry Cannon & Keith ; Meo, Gisella ; Morandi, Emilio ; Morgan, Robert C. ; Olbrich, Jürgen O. ; Paridaen, Sjoerd ; Perneczky, Géza ; Peters, Ursula ; Porter, Bern ; Ruch, Günther ; Shimamoto, Shozo ; Truck, Fred ; Ulrichs, Timm ; Van Dijk, Pier ; Joseph, Robert ; Van Kerckhoven, Anne-Mie ; Welch, Chuck ; Hoffberg, Judith A. ; Kovacs, Peter
Engels
Frans
Italiaans
Spaans
boek